Animal Welfarism in American Law: Animal Farming, Privilege, and Disempowerment - Cordeiro-Rodrigues, Luis (Archīum Ateneo, 2024)
The instrumentalization of rights and interests for furthering political and economic ends is a common phenomenon in contemporary societies. Routinely, these are a trojan horse to political goals that involve discrimination of disempowered groups. This phenomenon of instrumentalization is present in many social phenomena; a less explored phenomenon where this has been researched is this instrumentalization with respect to animal protection law. In this article, I explore how American animal law is instrumentalized to privilege the animal farming industry and disadvantage disempowered groups. I explain how American animal law tends to further disempower individuals according to class and perceived ethnicity. I present this argument by showing that the United States’ law treats animal farming practices differently from other animal practices, especially those practices of disadvantaged class and ethnic groups. Although some differences are sometimes morally justified, I argue that there is no plausible moral justification for this difference in treatment. Instead, all the arguments for exceptionalism can be refuted. I finish by presenting two sets of arguments to show that the hidden purpose of this different treatment is to facilitate and maintain the ongoing functioning of the animal farm industry while at the same time scapegoating disempowered groups as the agents of animal cruelty.